Implementasi Putusan MK Nomor 135/PUU-XIII Tahun 2015 Tentang Hak Pilih Disabilitas Mental Dalam Pemilu Perspektif Siyasah - Tri Ana Mardalisa; La Ode Muhammad Iman Abdi Anontomo Uke; Arini Pratiwi; Muhammad Najib (Institut Agama Islam (IAIN) Kendari, 2026)
This study examines the gap between the normative guarantee of voting rights for persons with mental disabilities and their implementation in elections, despite Constitutional Court Decision Number 135/PUU-XIII/2015, which affirms that mental disorders do not automatically eliminate a person’s capacity to vote. It aims to analyze the implementation of this decision from a siyasah perspective through a case study at the Southeast Sulawesi Provincial Mental Hospital. The research employs an empirical juridical method with a qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving hospital staff and the Kendari City General Election Commission. Data analysis was conducted through reduction, display, and conclusion drawing. The findings reveal that the implementation of voting rights for persons with mental disabilities still faces administrative and institutional obstacles. Voter registration remains incidental and unsustained, the absence of special or mobile polling stations limits access for inpatients, and the assessment of voting capacity is not supported by standardized operating procedures or adequate dissemination. These findings indicate that the main problem lies in technical governance rather than in the legal foundation itself. From a siyasah perspective, this condition reflects the incomplete realization of justice, trust, public welfare, and non-discrimination. The study highlights the importance of viewing mental hospitals as spaces for the exercise of political rights. Its implications include strengthening inter-institutional coordination, formulating joint standard operating procedures, conducting periodic voter registration, providing accessible polling mechanisms, and developing more inclusive, fair, and sustainable electoral policies for persons with mental disabilities at the local level.